Timoshenko Bending and Eshelby Twisting Predicted in Molecular Nanocrystals - Li, C.; Shtukenberg, A.; Carter, Damien; Cui, X.; Olson, I.; Rohl, Andrew; Gale, Julian; Raiteri, Paolo; Kahr, B. (American Chemical Society, 2018)
Well-formed crystals are polyhedral with flat facets and sharp edges. Nevertheless, a remarkable number of molecular crystals can bend and twist during growth. Many others can be distorted by applying external forces or creating heterogeneities by temperature gradient or photochemical reaction. As part of an effort to identify the forces that so commonly deform molecular crystals and to characterize their consequences, a force field is evaluated for its ability to predict mechanical distortions in nanocrystals. Macroscopic materials provide estimates of the expected responses that were tested here in silico for "molecular bimetallic strips" created from rods of iodoform and bromoform in smooth contact and nanocrystalline rods of iodoform with left and right screw dislocations. It was demonstrated that an optimized force field based largely on AMBER parameters matches expectations for elastic and plastic distortions, despite the fact that these mechanical responses are far removed from the force field parametrization set.